A Portable Controllable Compressive Stress Device to Monitor Human Breast Cancer Cell Protrusions at Single-Cell Resolution - Yeh, Chuan-Feng; Juang, Duane S.; Chen, Ya-Wen; Rodoplu, Didem; Hsu, Chia-Hsien (Frontiers in Bioengineering and Biotechnology, 2022)
In vitro devices offer numerous methods than in vivo models to investigate how cells respond to pressure stress and quantify those responses. Several devices have been developed to study the cell response to compression force. However, they are unable to observe changes in real time. There is also a concern about cell damage during the process of harvesting cells from 3D gels. Our device used transparency gel layers to clamp cells between the interfaces and applied a controllable compressive force by stacking multilayers on the top. In this approach, we monitored the alteration of cellular protrusions, whose diversity has been proved to promote cancer cell dissemination, with single-cell resolution imaging under compression stress. Furthermore, we implemented p-Rac-1 and rhodamine staining on the device directly to confirm the actin filament of lamellipodia. The method was able to fulfill real time live-cell observation at single-cell resolution and can be readily used for versatile cell analysis.